Assessment of a comprehensive aero-acousto-elastic solver for rotors in BVI conditions - Gennaretti, M.; Bernardini, G.; Serafini, J.; Romani, G. (My University, 2017)
The scope of this paper is the validation of the comprehensive aero-acousto-elastic solver developed in the last years at Roma Tre University against the well-known HART II database, which is the outcome of an international EU-US cooperative research project consisting of a wind tunnel experimental campaign for the measurements of loads, blade deflection, wake shape and noise concerning a 4-bladed model rotor in low-speed descent flight conditions. Comparisons ith numerical results available in the literature for the same test cases are also presented. The results provided by the Roma Tre solver are in good agreement with respect to experimental data, with a level of accuracy that is in line with the state-of-the-art predictions. The computational cost requested is limited.